ANALISIS PROFIL KETERAMPILAN PROSES SAINS PESERTA DIDIK PADA MATERI SUHU DAN PEMUAIAN - Hariandi, Joe; Sitompul, Stepanus Sahala; Habellia, Ray Cinthya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Education is an important element in life because education can strengthen one's self. Science learning is a learning that is a means of improving students' thinking skills. One of these abilities is the ability to be skilled in scientific processes. This study aims to determine the profile of students' science process skills at SMP Negeri 21 Pontianak on temperature and expansion. This form of research uses a quantitative descriptive method by providing test questions for students' science process skills. The sample of this research was class VII A, which consisted of 33 students. The results of this study were obtained from 33 students 30.30% were in the unskilled category, 60.60% were in the less skilled category, 9.09% were in the skilled category, and 0% were in the very skilled category and science process skills based on indicators is still low. So it is hoped that in the future it is hoped that students' science process skills can be improved through learning that is oriented to these science process skills.